Optical Design of a Retinal Image Acquisition Device for Mobile Diabetic Retinopathy Assessment - Melo, David Simões de (2018)
Diabetes mellitus is a condition that lead to various systemic alterations. These changes, taking place in the blood vessels cause a progressive capillary occlusion and, in the posterior eye region, provoke leakages from the vessels to the retina leading to a disease called diabetic retinopathy. This pathology ultimately can lead to complete vision loss, which is an aspect that emphasizes the relevance of the work developed in this thesis. The initial progression is asymptomatic, so only in advanced and frequently irreversible stages, the patient becomes aware of the disease. For this reason, a regular follow-up accomplished by eye fundus examination should be performed. Even though, for logistic motivations (lack of equipment, absence of ophthalmology specialists...) the progression-study and diagnose of the disease is often neglected. To encourage high coverage screening, a compact optical system was designed for a handheld and smartphone-based fundus camera prototype. The key features for the optical system are the low-cost achieved through a simple lens system and a mobile and non-mydriatic acquisition of fundus images with high field-of-view, by a smartphone camera. The simplicity of the optical system was accomplished by a three lens system setup. The results reveal a system with only a few aberrations in the periphery but with a good resolution at the center of a 41° field-of-view. Besides the optical system, a mechanical prototype was designed with the purpose of being 3D printed and easily portable. Also, a light hazard testing procedure was established and applied on a previously developed prototype. In the future, the implementation of the optical system in the prototype is intended, in order to confirm the applicability of the design in diminishing the burden of screening actions and consequently, empower the early treatment of the pathology.